Solar Ultraviolet Radiation-Induced DNA Damage And Protection/Repair Strategies In Cyanobacteria - RAJESH P. RASTOGI; RAJESHWAR P. SINHA (International Journal of Pharma and Bio Sciences, 2011)
Ultraviolet radiation (UVR) coming from the Sun is an ever-present stress for living organisms including cyanobacteria that damages several biological processes either directly or indirectly through the formation of reactive oxygen species (ROS). DNA is one of most prominent target for UVR. A number of mutagenic and cytotoxic DNA lesions such as cyclobutane-pyrimidine dimers (CPDs), 6-4 photoproducts (6-4PPs), and their Dewar valence isomers as well as DNA strand breaks produced by means of solar UVR (particularly UV-B; 280-315 nm) can alter the genome integrity and affect the normal life process of all organisms. Cyanobacteria cope with UVR either through a combination of repair mechanisms such as photoreactivation, excision repair, recombinational repair, SOS response and apoptosis/programmed cell death (PCD) or by production of certain UV-absorbing/screening compounds such as mycosporine-like amino acids (MAAs) and scytonemin. Besides the above mentioned photoprotective mechanisms several other defence strategies such as avoidance and production of anti-oxidants are also operative in cyanobacteria against UVR. In the present review we discuss only the effects of UVR on DNA and protection/repair strategies applied by cyanobacteria against UVR.